The Prevalence, Risk, and Management of Methicillin-Resistant Staphylococcus aureus Infection in Diverse Populations across Canada: A Systematic Review - Elena Mitevska; Britney Wong; Bas G. J. Surewaard; Craig N. Jenne (Pathogens, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) first emerged after methicillin was introduced to combat penicillin resistance, and its prevalence in Canada has increased since the first MRSA outbreak in the early 1980s. We reviewed the existing literature on MRSA prevalence in Canada over time and in diverse populations across the country. MRSA prevalence increased steadily in the 1990s and 2000s and remains a public health concern in Canada, especially among vulnerable populations, such as rural, remote, and Indigenous communities. Antibiotic resistance patterns and risk factors for MRSA infection were also reported. All studies reported high susceptibility (>85%) to trimethoprim-sulfamethoxazole, with no significant resistance reported for vancomycin, linezolid, or rifampin. While MRSA continues to have susceptibility to several antibiotics, the high and sometimes variable resistance rates to other drugs underscores the importance of antimicrobial stewardship. Risk factors for high MRSA infection rates related to infection control measures, low socioeconomic status, and personal demographic characteristics were also reported. Additional surveillance, infection control measures, enhanced anti-microbial stewardship, and community education programs are necessary to decrease MRSA prevalence and minimize the public health risk posed by this pathogen.